The 2020 Updated KDOQI Clinical Practice Guidelines for Nutrition in Chronic Kidney Disease - Ikizler, Talat Alp; Cuppari, Lilian (Blood purification, 2021)
Abstract Over the last 2 decades, there has been a great accumulation of new evidence regarding the management of nutritional and metabolic aspects of kidney disease. The 2020 update to the KDOQI Clinical Practice Guideline for Nutrition in CKD provides a comprehensive up-to-date information on the understanding and care of patients with CKD. It provides updated information on nutritional aspects of kidney disease for the practicing clinician and allied health-care workers. The current manuscript provides an overview of the updated guideline statements on major subjects including nutritional assessment, dietary protein and energy intake, nutritional supplementation, micronutrients, and electrolytes. The guidelines are focused on dietary management rather than all possible nutritional interventions.